2019
DOI: 10.21053/ceo.2018.01781
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Breastfeeding in the Prevention of Allergic Rhinitis: Allergic Rhinitis Cohort Study for Kids (ARCO-Kids Study)

Abstract: Objectives There is a great deal of interest in the possibility that environmental factors may influence the risk of developing allergic rhinitis (AR) in early life. We investigated the simultaneous effects of mode of delivery and duration of breastfeeding on the development of AR in children. Methods Data from 1,374 children participating in the Allergic Rhinitis Cohort Study for kids (ARCO-kids study) was analyzed. All subjects were divided into AR or non-allergic rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Our ndings are consistent with most previous studies in which CS delivery, only one child in the household and formula feeding were associated with an increased risk of allergic diseases among children [6][7][8][12][13][14][15][16][17][18]. Recently, a systematic review and meta-analysis reported that male sex, short duration of breastfeeding and having siblings were risk factors of early transient wheezing among children aged 3-18 years) [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our ndings are consistent with most previous studies in which CS delivery, only one child in the household and formula feeding were associated with an increased risk of allergic diseases among children [6][7][8][12][13][14][15][16][17][18]. Recently, a systematic review and meta-analysis reported that male sex, short duration of breastfeeding and having siblings were risk factors of early transient wheezing among children aged 3-18 years) [19].…”
Section: Discussionsupporting
confidence: 92%
“…Another study in Shanghai found that CS without medical indication was associated with increased risks of both childhood asthma and AR, and breastfeeding in early infancy attenuated these risks [6]. The Allergic Rhinitis Cohort Study for kids conducted in South Korea found that long-term breastfeeding (≥ 12 months) and a vaginal delivery were associated with a lower risk of developing childhood AR [7]. However, in two unselected populations using harmonised protocols in Australia, the association of CS with developing childhood allergy was weak, and no modi cation effects by breastfeeding duration were found [9].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have confirmed that Cesarean births correlate with an increased incidence of FA and asthma [5,6,[22][23][24]. The latest American cohort study in children born in the state of New York (n = 1356) in the years 2008-2010 showed that emergency C-section delivery was associated with a higher relative risk (RR) of wheezing (RR = 2.47, 95% CI 1.31-4.66) and FA (RR = 3.02, 95% CI 1.26-7.25) [22].…”
Section: Cesarean Sections the Microbiota And Allergy Developmentmentioning
confidence: 95%
“…Allergic rhinitis markedly affects patients' quality of life, and it is a major reason for outpatient visits to otolaryngology clinics [1][2][3][4][5]. Allergic rhinitis is generally thought to be mediated by Th2, with interleukin (IL)-4, IL-5, and IL-13 also contributing to its pathogenesis [6].…”
Section: Introductionmentioning
confidence: 99%